EXPLORING THE DYNAMIC INFLUENCE OF PERCEIVED BRAND GLOBALNESS AND LOCALNESS: A CASE STUDY ON HIGH-INVOLVEMENT GOODS - Sembhodo, Abimanyu Tuwuh; Sumiyarto, Sumiyarto; Widiastri, Dwi; Fauzan, Rushli (Universitas Brawijaya, Indonesia, 2023)
This study ventures into unexplored research territory, effectively bridging a considerable knowledge gap surrounding the application of perceived brand globalness and perceived brand localness as branding strategies, particularly concerning high involvement goods in the Indonesian market. Employing a quantitative descriptive research approach, this study utilizes Partial Least Squares-Structural Equation Modeling (PLS-SEM) analysis to unravel its insights. The analysis outcomes divulge that both perceived brand globalness and perceived brand localness wield substantial direct influence on marketing success, as gauged by variables encompassing brand loyalty, positive word of mouth, and willingness to pay a premium price. Remarkably, this influence is more pronounced for brands perceived on a global scale. Intriguingly, the study uncovers brand trust as a pivotal mediator in this connection, exerting a more potent influence compared to the direct relationship. This mediating role proves particularly accentuated for brands perceived as local.The discoveries of this study bear pragmatic implications for local brands, illuminating the efficacy of leveraging perceived brand globalness and perceived brand localness as potent branding strategies, alongside their corresponding influencing factors.